مخاطر مهنة الراجعة على جودة المراجعة : دراسة تحليلية لآراء عينة من المراجعين الخارجيين في الجزائر - زين, يونس; زين, عيسى (جامعة الوادي University of Eloued, 2016)
تهدف هذه الدراسة إلى التعرف على أثر مخاطر مهنة المراجعة على جودة المراجعة، وإبراز مدى أهمية جودة المراجعة بغية المساهمة في تحسين خدمات مكاتب المراجعة بالجزائر، وهذا من خلال دراسة تحليلية للآراء عينة من المراجعين الخارجيين بالجزائر، وأجريت باستخدام استبيان تم تصميمه بالاعتماد على الدراسات السابقة والدراسة النظرية ووزعت على عينة من مراجعين الخارجيين بالجزائر، وقد خلصت هذه الدراسة إلى أن تقليل من المخاطر الملازمة ومخاطر الرقابة ومخاطر الاكتشاف يزيد من جودة المراجعة. This study aimed mainly to show the impact of Audit Risk on audit quality, highlighting the importance of audit quality in order to contribute to the improvement of services the External Auditors in Algeria. This is through the analytical study of the views of a sample of external auditors in Algeria. Also it was conducted using a questionnaire was designed based on previous studies and theoretical study was distributed to a sample of external auditors in Algeria. This study has concluded that reduce the risks inherent risk, control and risk discovery increases the quality of the audit.
The impact of Audit Risk on audit quality "Analytical Study: A sample of the External Auditor In Algeria"
مقال- مجلة رؤى اقتصادية
Keywords: مخاطر المراجعة، جودة المراجعة، المراجع الخارجي، مخاطر الملازمة، مخاطر الرقابة، مخاطر الاكتشاف; Audit Risk, audit quality, External Auditor, inherent risks, control risks, detection risks